Comparison of Maternal Feeding Practices and Child Weight Status in Children from Three Countries - Williams, Keith E.; Petty, Maria Blanques; Schimith-Escrivão, Maria Arlete M.; Chung, Kyong-Mee; Jung, Woo Hyun; Hendy, Helen M. (International Journal of Child Health and Nutrition, 2014)
The present study considered three samples of mothers from Brazil, South Korea, and the United States to determine whether mothers demonstrate a consistent pattern of feeding practices associated with child overweight. Participants included 1204 mothers of children 6-10 years old. Mothers completed questionnaires to report their children’s demographics and their feeding practices with the Parent Mealtime Action Scale (PMAS). The South Korean children showed significantly less obesity (10.4%) than children from Brazil (17.0%) or the United States (19.6%). Confirmatory factor analysis for mothers from all three samples revealed good fit for the same nine PMAS dimensions of feeding practice. Hierarchical multiple regression revealed that after taking into account child age and gender, heavier child weight was found associated with more Fat Reduction and less Insistence on Eating by mothers from all three samples. Results from past experimental research suggest that these two maternal feeding practices would be counter-productive for teaching children’s self-regulation of diet and weight management. Alternative maternal feeding practices are suggested.